Biosorption of Pb(II), Ni(II) and Cr(VI) ions from aqueous solution using Rhizoclonium tortuosum: extended application to nickel plating industrial wastewater. Issue 52 (7th November 2016) - Suganya, S.; Kayalvizhi, K.; Senthil Kumar, P.; Saravanan, A.; Vinoth Kumar, V.
Abstract: The adsorption of Pb(II), Ni(II), and Cr(VI) ions onto Rhizoclonium tortuosum (RT) was investigated in a batch mode operation. The two parameter (Langmuir and Freundlich) and three parameter models (Redlich–Peterson and Sips isotherm model) were used to depict the adsorption of metal ions onto R. tortuosum . Sips isotherm model was provided the best fit to the adsorption equilibrium data. The adsorption kinetics was described by the pseudo-first-order, pseudo-second-order, and Elovich kinetic models. The pseudo-second-order model provides the best fit. The maximum monolayer adsorption capacity of the RT were found to be 66.08, 85.09, and 61.45 mg/g for Pb(II), Ni(II), and Cr(VI), respectively. The thermodynamic results showed that the adsorption process was endothermic, feasible, and spontaneous in nature. The ability of RT to remove the Ni(II) ions in column studies was explored. The effect of bed height, flow rate, and initial Ni(II) ion concentration were studied. The dynamic behavior of the column performance was studied using the bed depth service time (BDST) and Thomas models. This research was also further extended to treat the nickel contaminated plating industrial wastewater. The results showed that the RT can be utilized as better biosorbent for the removal of metal ions from industrial wastewater.